Mechanism and efficiency of photocatalytic triclosan degradation by TiO2/BiFeO3 nanomaterials - Liu, Gen (Water science and technology : a journal of the International Association on Water Pollution Research, 2022)
Hierarchical porous TiO2 photocatalytic nanomaterials were fabricated by impregnation and calcination using a peanut shell biotemplate, and TiO2/BiFeO3 composite nanomaterials with different doping amounts were fabricated using hydrothermal synthesis. The micromorphology, structure, element composition and valence state of the photocatalyst were analyzed using a series of characterization methods, including X-ray diffraction (XRD), scanning electron microscope (SEM), transmission electron microscope (TEM), BET surface area (BET), X-ray photoelectron spectroscopy (XPS), UV-visible diffuse reflectance (UV-vis), fluorescence spectroscopy (PL) and other technological means. Finally, the degradation mechanism and efficiency of BiFeO3 composite photocatalyst on the target pollutant triclosan were analyzed using a xenon lamp to simulate sunlight. The results showed that TiO2/BiFeO3 catalyst fabricated using a peanut shell biotemplate has a specific surface area of 153.64 m2/g, a band gap of 1.92 eV, and forms heterostructures. The optimum doping amount of TiO2/BiFeO3 catalyst was 1 mol/mol, and the degradation rate was 81.2%. The main active substances degraded were ·O2-and ·OH. The degradation process measured is consistent with the pseudo-first-order kinetic model